Analysis of various conditions in order to measure electromyography of isometric contractions in water and on air - da Silva Carvalho, Rodrigo Gustavo; Amorim, Cesar Ferreira [UNESP]; Rossi Peracio, Luis Henrique; Coelho, Helder Figueiredo; Vieira, Andre Carleone; Menzel, Hans-Joachim Karl; Szmuchrowski, Leszek Antoni (Elsevier B.V., 2010)
The aim of this study was to verify if there are differences in the amplitude of signals from surface electromyography (EMG) during maximal and submaximal voluntary isometric contraction (MVC and 50% MVC, respectively) under different conditions, in our case, water and air, with and without extra protection (water-resistant tape) on the electrode. The isometric force and muscle activation of the MVC and 50% MVC of the biceps brachial muscle of nine healthy trained men were measured simultaneously, performed in water and on air, with and without protection of the EMG electrode. The multivariate analysis of variance with a post hoc Tukey test was applied to detect significant differences between the levels of muscular force. For the amplitude values of the EMG signal, the Wilcoxon signed rank test was applied to compare all experimental conditions in order to detect a significance of p < 0.05. The values of isometric force were not significantly different among conditions (MVC and 50% MVC). The results showed a significant difference among conditions in the water without extra protection compared to the conditions on air with and without extra protection and in water with extra protection. Reduced EMG amplitude was seen in water without extra protection from 37.04% to 55.81% regarding the other conditions. However, no significant difference was seen among conditions in water with extra protection in relation the conditions on air (with and without extra protection). This study suggest that it is necessary to use a water-resistant tape as an extra protection on the electrode when using EMG underwater, to avoid having a significant decrease in the EMG amplitude underwater and not to suffer interference from the water. There was no significant difference among the recordings of EMG with and without the use of protection on air; therefore, the protection does not influence the recording of EMG amplitude and isometric force on air. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Electromyography; Isometric force; EMG signal amplitude; EMG water recording